ANALYSIS OF THE ROLE OF SANTRI IN THE DEVELOPMENT OF PESANTREN BUSINESS UNITS (CASE STUDY OF DARUNNAJAH ISLAMIC BOARDING SCHOOL, SOUTH JAKARTA) - Sri Sudiarti; Wahyu Sarvina; Nurul Jannah (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Pesantren is a school that teaches religious sciences, Initially, pesantren only taught religious knowledge, but for now there are modern pesantren that combine religious knowledge with general knowledge, Darunnajah Islamic Boarding School is one of the modern pesantren, So the leadership of the pesantren also uses this opportunity to open a business unit to teach students self-reliance and entrepreneurial education, so that students are expected to play an active role in the management of the business unit being run. This study uses descriptive qualitative methods and data collection is carried out by means of in-depth interviews. The results of this study reveal that Darunnajah Islamic boarding school students play an active role in the development of business units run by Islamic boarding schools, The role played by the students is to become a business unit manager and provide bright ideas that they have to develop their business units.